2011
DOI: 10.1007/s11033-011-1362-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Polycomb group genes in the silkworm, Bombyx mori

Abstract: Polycomb group (PcG) proteins are involved in chromatin modifications for maintaining gene repression that play important roles in the regulation of gene expression, tumorigenesis, chromosome X-inactivation, and genomic imprinting in Drosophila melanogaster, mammals, and even plants. To characterize the orthologs of PcG genes in the silkworm, Bombyx mori, 13 candidates were identified from the updated silkworm genome sequence by using the fruit fly PcG genes as queries. Comparison of the silkworm PcG proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…F r d ub e-stranded RNA (dsRNA) synthesis, all the fragments were amplified from the first-strand cDNA using the gene-specific primers i c udi g a additi a T7 pr m ter seque ce at b th 5' a d 3' termi us isted i Table 3). The dsRNAs were synthesized by in vitro transcription with T7 RNA polymerase (TakaraBio, Shiga, Japan) as described previously (Li et al, 2012). The soaking RNAi in Bm5-SID1 cells were performed according to our previous study .…”
Section: Rna Interference Cell Proliferation Assay and Reporter Assaymentioning
confidence: 99%
“…F r d ub e-stranded RNA (dsRNA) synthesis, all the fragments were amplified from the first-strand cDNA using the gene-specific primers i c udi g a additi a T7 pr m ter seque ce at b th 5' a d 3' termi us isted i Table 3). The dsRNAs were synthesized by in vitro transcription with T7 RNA polymerase (TakaraBio, Shiga, Japan) as described previously (Li et al, 2012). The soaking RNAi in Bm5-SID1 cells were performed according to our previous study .…”
Section: Rna Interference Cell Proliferation Assay and Reporter Assaymentioning
confidence: 99%
“…Partial cDNA fragments for the silkworm genes were amplified using specific primers (Table 1) and cloned into a dual T7 promoter-driven vector of pLits [21]. The pLits vector containing the silkworm cDNAs was used to synthesize double-stranded RNA (dsRNA) by T7 RNA polymerase in vitro and the RNA interference (RNAi) treatments were performed in above described cell lines according to our previous studies [21,22].…”
Section: Rna Interference For Er Chaperone Genesmentioning
confidence: 99%
“…The pLits vector containing the silkworm cDNAs was used to synthesize double-stranded RNA (dsRNA) by T7 RNA polymerase in vitro and the RNA interference (RNAi) treatments were performed in above described cell lines according to our previous studies [21,22].…”
Section: Rna Interference For Er Chaperone Genesmentioning
confidence: 99%
“…We previously identified the conserved 13 PcG genes in the silkworm, Bombyx mori [16]. Interestingly, our microarray analysis revealed that the asparagine synthetase ( ASNS ) gene is similarly up-regulated after RNA interference (RNAi)-meditated knockdown of some PcG genes, such as BmSCE , BmESC , BmPHO , and BmSCM (encoding a protein that can interact with BmPho and contribute to transcriptional repression), in silkworm cells [17].…”
Section: Introductionmentioning
confidence: 96%